Question
upstudy study bank question image url

Resolver las siguientes ecuaciobes, aplicando la formu general \( \quad \frac{-b \pm \frac{\sqrt{b^{2}-4 a c}}{2 a}}{} \begin{array}{l}\text { a } \\ \text { a) } 16 x^{2}-4 x-13=0\end{array} \)

Ask by Marsh Haynes. in Ecuador
Jan 09,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

Las soluciones son \(x_{1}=\frac{1-\sqrt{53}}{8}\) y \(x_{2}=\frac{1+\sqrt{53}}{8}\).

Solution

Solve the equation \( 16x^2-4x-13=0 \). Solve the quadratic equation by following steps: - step0: Solve using the quadratic formula: \(16x^{2}-4x-13=0\) - step1: Solve using the quadratic formula: \(x=\frac{4\pm \sqrt{\left(-4\right)^{2}-4\times 16\left(-13\right)}}{2\times 16}\) - step2: Simplify the expression: \(x=\frac{4\pm \sqrt{\left(-4\right)^{2}-4\times 16\left(-13\right)}}{32}\) - step3: Simplify the expression: \(x=\frac{4\pm \sqrt{848}}{32}\) - step4: Simplify the expression: \(x=\frac{4\pm 4\sqrt{53}}{32}\) - step5: Separate into possible cases: \(\begin{align}&x=\frac{4+4\sqrt{53}}{32}\\&x=\frac{4-4\sqrt{53}}{32}\end{align}\) - step6: Simplify the expression: \(\begin{align}&x=\frac{1+\sqrt{53}}{8}\\&x=\frac{4-4\sqrt{53}}{32}\end{align}\) - step7: Simplify the expression: \(\begin{align}&x=\frac{1+\sqrt{53}}{8}\\&x=\frac{1-\sqrt{53}}{8}\end{align}\) - step8: Rewrite: \(x_{1}=\frac{1-\sqrt{53}}{8},x_{2}=\frac{1+\sqrt{53}}{8}\) Las soluciones de la ecuación \(16x^2-4x-13=0\) son \(x_{1}=\frac{1-\sqrt{53}}{8}\) y \(x_{2}=\frac{1+\sqrt{53}}{8}\).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

Para resolver la ecuación \(16x^{2}-4x-13=0\) usando la fórmula general, primero identificamos los coeficientes: \(a = 16\), \(b = -4\) y \(c = -13\). Ahora, calculamos el discriminante \(b^{2}-4ac\): \[ b^{2} = (-4)^{2} = 16 \] \[ 4ac = 4 \cdot 16 \cdot (-13) = -832 \] \[ b^{2}-4ac = 16 + 832 = 848 \] Luego, sustituimos en la fórmula general: \[ x = \frac{-(-4) \pm \sqrt{848}}{2 \cdot 16} = \frac{4 \pm \sqrt{848}}{32} \] Simplificando \(\sqrt{848}\): \[ \sqrt{848} = \sqrt{16 \cdot 53} = 4\sqrt{53} \] Entonces, la solución es: \[ x = \frac{4 \pm 4\sqrt{53}}{32} = \frac{1 \pm \sqrt{53}}{8} \] Las raíces son \(x_1 = \frac{1 + \sqrt{53}}{8}\) y \(x_2 = \frac{1 - \sqrt{53}}{8}\). ¡Y así se resuelven las ecuaciones! 🎉

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy